2020
DOI: 10.1111/jen.12787
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an oil‐based formulation combining Metarhizium rileyi and nucleopolyhedroviruses against lepidopteran pests of soybean

Abstract: A biopesticide that combines Metarhizium rileyi and nucleopolyhedrovirus (NPV) in an oil dispersion (OD) was developed. Its efficacy against Anticarsia gemmatalis and Chrysodeixis includens was evaluated under laboratory and field conditions. First, each of the two selected fungal strains, combined or not in OD preparations with AgMNPV or ChinNPV, was tested in the laboratory against A. gemmatalis and C. includens, respectively. AgMNPV–fungus combinations had similar effect on overall mortality of A. gemmatali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The absence of a synergistic effect has already been reported in laboratory experiments when selected isolates of M. rileyi and NPV were used in combination against S. frugiperda or A. gemmatalis 31 . However, Lopes et al 50 . discussed the potential positive effect that a dual‐action biopesticide would have to manage mixed populations of lepidopteran pests through the combination of NPV and M. rileyi .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The absence of a synergistic effect has already been reported in laboratory experiments when selected isolates of M. rileyi and NPV were used in combination against S. frugiperda or A. gemmatalis 31 . However, Lopes et al 50 . discussed the potential positive effect that a dual‐action biopesticide would have to manage mixed populations of lepidopteran pests through the combination of NPV and M. rileyi .…”
Section: Discussionmentioning
confidence: 98%
“…The absence of a synergistic effect has already been reported in laboratory experiments when selected isolates of M. rileyi and NPV were used in combination against S. frugiperda or A. gemmatalis. 31 However, Lopes et al 50 discussed the potential positive effect that a dual-action biopesticide would have to manage mixed populations of lepidopteran pests through the combination of NPV and M. rileyi. Field experiments in that study suggested that a fungal isolate in the mixture capable of infecting a wide range of hosts may kill caterpillars not susceptible to the virus, or those insects that may not have ingested the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rhizosphere soils from high yield sites at both SGS contained greater percentages of genus Metarhizium ( M. anisopliae and M. marquandii ) compared to low yield sites. The beneficial entomopathogenic behavior of Metarhizium including M. anisopliae and M. marquandii is widely documented in relation to soybean production ( Clifton et al, 2018 ; Baron et al, 2020 ; Lopes et al, 2020 ). Therefore, the greater occurrence of beneficial fungal genera such as Trichoderma and Metarhizium can potentially eases the soilborne pathogen and insect pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, M. riley is an entomopathogenic fungus with a great potential to control noctuid pests in several agricultural systems. For instance, C. includens and S. frugiperda larvae are susceptible to this entomopathogen, and the occurrence of natural epizootics caused by M. rileyi on these pest species is often observed in soybean and corn crops, respectively (Pavone et al 2009, Sosa-Gómez 2017, Souza et al 2019, Lopes et. al.…”
Section: Abstract Resumomentioning
confidence: 99%